APLIKASI BIOHERBISIDA EKSTRAK SERASAH DAUN BAMBU (Dendrocalamus sasper) UNTUK MENGHAMBAT PERTUMBUHAN GULMA SEMBUNG RAMBAT (Mikania micrantha) - Novitasari, Padia; Jatsiyah, Venti; Ratnawati Hermanto, Sarwendah; Kurniawan, Tardi (Journal of Agro Plantation (JAP), 2024)
Sembung rambat weed (Mikania micrantha) is a weed that grows in immature oil palm plantations. One of the raw materials that can be used as a bioherbicide is bamboo leaf litter extract (Dendrocalamus sasper L.) because it contains coumarin compounds, flavonoids, anthraquinones, polysaccharides, phenolics and amino acids. This study aims to determine whether the administration of bamboo leaf litter extract can inhibit the growth of sembung rambat weeds and determine the concentration of bamboo leaf litter extract that is effective in inhibiting the growth of sembung rambat weeds. This study used a non-factorial Completely Randomized Design (CRD), consisting of 6 levels of treatment concentration K0 = Control, K1 = 5%, K2 = 10%, K3 = 15%, K4 = 25% and K5 = 35 with 5 replications. so that 30 experimental units were obtained where each experimental unit sample consisted of 3 samples so that the total number was 90 samples of weeds on the growth of sembung rambat weeds with the observation parameters of plant height, number of leaves, day of death, wet weight, dry bering and root length. The results of variance showed that the application of bamboo leaf litter extract had a significant effect on plant height, number of leaves, day of death, wet weight, dry weight and root length. The concentration of bamboo leaf litter extract that was effective in inhibiting the growth of sembung rambat weeds was a 25% concentration of bamboo leaf litter extract.